Mathematics Teaching in the Digital Age: Teachers’ Perspectives on the Use of MATLAB in BCA Program of T.U. - Sapkota, Buddhi Prasad (Academic Journal of Mathematics Education, 2024)
The incorporation of digital tools in the teaching-learning process is transforming the methods of teaching mathematics, which is grounded in logic and computation. MATLAB is a powerful, high-performance language for technical computing, mathematical modelling, data analysis, simulation, etc. The study examines the perspectives on the use of MATLAB in mathematics instruction, highlighting knowledge and use, which has the potential to increase student engagement and improve problem-solving skills. The findings suggest that information and communication technology (ICT)/MATLAB can significantly enrich mathematics teaching. Although 64.8% of the teachers were familiar with MATLAB, only 22.2% actively used it in their classrooms. The study highlights key challenges, including a lack of practical courses, limited resources, and insufficient training. Despite these challenges, most teachers (60.2%) expressed satisfaction with their teaching roles. The analysis revealed a significant association between access to computer labs and familiarity with MATLAB, whereas no significant associations were found between knowledge of MATLAB and age or gender. Teachers believe that enhanced engagement, visual representation of mathematical concepts, and support for self-directed collaborative learning is some of the benefits of incorporating ICT/MATLAB for effective teaching and learning.